Electro-blown micro-nanofibrous mats with Origanum elongatum essential oil for enhancing the shelf life of tomato ( Solanum lycopersicum ) - Akhouy, Ghizlane; Eticha, Andinet Kumella; Dogan, Cemhan; Dogan, Nurcan; Calisir, Mehmet D.; Toptas, Ali; Aziz, Faissal; Akgul, Yasin (Oxford University Press (OUP), 2024)
Abstract This study aims to develop a novel active food packaging material from hybrid micro-nanofibrous mats fabricated from gelatin (G)–chitosan (Ch)–polyvinyl alcohol (PVA)–Origanum elongatum essential oil (EO), (G-Ch-PVA-EO) through electro-blowing. The fibrous mats were characterised to assess their morphologies, shelf life efficiency, antimicrobial and antioxidant properties, surface-wetting, and thermal, chemical, and physical interactions, among other factors. Results showed that the antioxidant activity was improved with the addition of EO, this enhancement is potentially linked to its rich content of phenolic components; carvacrol and P-cymene. In addition, G-Ch-PVA-EO showed higher firmness measurements compared to the control samples. Herein, low microbial counts were noted for both mesophilic aerobic bacteria (3.76 log CFU g−1) and yeast/mould (3.91 log CFU g−1) even at day 20. To conclude, the G-Ch-PVA-EO microfibrous mat exhibits great promise in preserving the freshness of tomatoes.